Multi-functional polymeric micelles for chemotherapy-based combined cancer therapy. Issue 42 (12th October 2021) - Bholakant, Raut; Dong, Bin; Zhou, Xiang; Huang, Xin; Zhao, Changshun; Huang, Dechun; Zhong, Yinan; Qian, Hongliang; Chen, Wei; Feijen, Jan
Abstract : Schematic diagram of multi-functional PMs for chemotherapy-based combined cancer therapy: combination of multiple chemotherapy drugs; combinational chemo-gene therapy; combinational chemo-phototherapy; combinational chemo-immunotherapy. Abstract : Currently, the therapeutic performance of traditional mono-chemotherapy on cancers remains unsatisfactory because of the tumor heterogeneity and multidrug resistance. In light of intricate tumor structures and distinct tumor microenvironments (TMEs), combinational therapeutic strategies with multiple anticancer drugs from different mechanisms can synergistically optimize the outcomes and concomitantly minimize the adverse effects during the therapy process. Extensive research on polymeric micelles (PMs) for biomedical applications has revealed the growing importance of nanomedicines for cancer therapy in the recent decade. Starting from traditional simple delivery systems, PMs have been extended to multi-faceted therapeutic strategies. Here we review and summarize the most recent advances in combinational therapy based on multifunctional PMs including a combination of multiple anticancer drugs, chemo-gene therapy, chemo-phototherapy and chemo-immunotherapy. The design approaches, action mechanisms and therapeutic applications of these nanodrugs are summarized. In addition, we highlight the opportunities and potential challenges associated with this promising field, which will provide new guidelines for advanced combinational cancer chemotherapy.